2014
DOI: 10.1136/bmjopen-2013-004222
|View full text |Cite
|
Sign up to set email alerts
|

Have restricted working hours reduced junior doctors’ experience of fatigue? A focus group and telephone interview study

Abstract: ObjectiveTo explore the effects of the UK Working Time Regulations (WTR) on trainee doctors’ experience of fatigue.DesignQualitative study involving focus groups and telephone interviews, conducted in Spring 2012 with doctors purposively selected from Foundation and specialty training. Final compliance with a 48 h/week limit had been required for trainee doctors since August 2009. Framework analysis of data.Setting9 deaneries in all four UK nations; secondary care.Participants82 doctors: 53 Foundation trainees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 66 publications
0
35
0
5
Order By: Relevance
“…Many causes of burnout derive from organizational-and system-level factors, including electronic health records (EHRs (5), 33,47,52,54,57 Canada (2), 42,48 Egypt (1), 53 and multinational (2). 24,35 Study designs included randomized controlled trials (10), 23,28,29,37,39,40,42,45,48,51 prospective studies (5), 43,44,50,56,60 cross-sectional studies (7), 19,38,47,52,53,66,68 and other designs (4). 24,27,35,59 The included studies evaluated interventions among primary care physicians and residents (12) 31,63,66 and groups of physicians with specialty unspecified (7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many causes of burnout derive from organizational-and system-level factors, including electronic health records (EHRs (5), 33,47,52,54,57 Canada (2), 42,48 Egypt (1), 53 and multinational (2). 24,35 Study designs included randomized controlled trials (10), 23,28,29,37,39,40,42,45,48,51 prospective studies (5), 43,44,50,56,60 cross-sectional studies (7), 19,38,47,52,53,66,68 and other designs (4). 24,27,35,59 The included studies evaluated interventions among primary care physicians and residents (12) 31,63,66 and groups of physicians with specialty unspecified (7).…”
Section: Resultsmentioning
confidence: 99%
“…56 Two studies 34,64 provided qualitative findings, and 10 studies did not report the instrument used to measure burnout. 31,35,36,41,43,46,47,59,60,67…”
Section: Measures Of Burnoutmentioning
confidence: 99%
See 1 more Smart Citation
“…Extended work hours are known to result in fatigue and fatigue‐related medical errors . Fatigue has been shown to affect postgraduate trainees’ performance, learning, and patient safety . Desai et al (2013) have demonstrated increased sleep duration when compliance with duty hour regulations implemented by American Council for Graduate Medical Education in 2011 is achieved, but the impact on patient care or trainee well‐being remains controversial .…”
Section: Introductionmentioning
confidence: 99%
“…1 Fatigue has been shown to affect postgraduate trainees' performance, learning, and patient safety. 2 for Graduate Medical Education in 2011 is achieved, 4 but the impact on patient care or trainee well-being remains controversial. 5 On the contrary, Japanese postgraduate training programs are not mandated to report trainees' work hours although Japanese government issued a guideline for work hours and standard labor act in 2005.…”
Section: Introductionmentioning
confidence: 99%